TAMAN EDUKASI PANGERAN ANTASARI DENGAN PENDEKATAN NEO-VERNAKULAR KOTA BANJARMASIN - Mudzakky, Abdy Ikhwan; Sarbini, Gusti Novi (JURNAL TUGAS AKHIR MAHASISWA LANTING, 2023)
In urban areas, getting information from existing technology is very easy to do. However, it is a little difficult to become dependent for early childhood children who are still not psychologically stable. History is also a part of the information that is easily available at this time. One of the famous historical figures from Banjarmasin is Prince Antasari. Prince Antasari is a National Hero of the kingdom of Banjar in his resistance to the Dutch troops. This makes the history of Prince Antasari need to be known by the people of Banjar itself, especially among children. One way of delivering this information without the need for digital technology is through Educational Parks. The approach that will be applied to the Educational Park is the Neo-Vernacular approach. This approach will find unique things that exist in the Banjar traditional building and apply it to the design of the “Prince Antasari Educational Park with a Neo-Vernacular Approach in Banjarmasin City”.